Antimicrobial Effect of Copper Nanoparticles Synthesized by Chemical Method - Hona, Salina; Dangol, Rebecca; Ghatane, Janaki; Giri, Dinesh; Pradhananga, Raja Ram (International Journal of Applied Sciences and Biotechnology, 2019)
Copper nanoparticles were synthesized by chemical reduction of copper sulphate pentahydrate with sodium borohydride at ambient temperature in presence of PEG (Polyethylene Glycol) as protective agent and ascorbic acid as antioxidant. The synthesized copper nanoparticles were characterized by FT-IR to determine the presence of different functional groups attached to copper nanoparticles. Their optical property was determined by UV-Vis absorption spectrum where the peak was observed at 320 nm. The crystalline structure and surface morphology of copper nanoparticles were investigated by XRD and SEM respectively. The average crystalline size of nanoparticles calculated by Debye Scherer formula was found to be less than 10 nm having cubical shape. Microbial investigations by macro broth dilution, growth kinetics analysis and disc diffusion method confirmed antimicrobial nature of copper nanoparticles. The study reveals that concentration of copper nanoparticles at 128 ppm shows bacteriostatic effect. Their anti fungal effect was evaluated by testing against Alternaria species. The maximum inhibitory effect was found when copper nanoparticle concentration was 400 ppm or more. Int. J. Appl. Sci. Biotechnol. Vol 7(4): 421-428